الإصابات الرضية لدى طلاب كلية التربية الرياضية بجامعة تشرين دراسة تحليلية - علي ناظم (Latakia University Journal -Medical Sciences Series, 2017)
يعتبر البحث دراسة مسحية تهدف إلى معرفة أنواع الإصابات الرياضية لدى طلاب كلية التربية الرياضية بجامعة تشرين وأسبابها . وقد شملت الدراسة(110) مصابا من أصل)930) طالبا وهو المجتمع الكلي للدراسة. وكانت النتائج كالتالي : • الأطراف السفلية هي الأكثر إصابة وخاصة مفصلي الركبة والكاحل . • النسبة العليا من الإصابات كانت في السنوات الأولى )السنة الأولى و الثانية). • من أهم الأسباب نقص الإحماء وعدم كفاية التحضير. • نسبة الإصابات أكثر ارتفاعا في العاب القوى يليها الجمباز . The research aimed to know different kinds of sportive injuries the students of sport faculty of tishreen university have ,and the reasons behind them . The study have involved (110) scorbutics out of (930) students which is the total society of the study . The results were as follows : - The lower extremities are the most affected especially the knee and ankle joint. - The biggest percentage was in the first years ( first and second year). - The most important reasons are overheating shortage and the lack of preparation. The injures biggest rate is in athletics then comes the gymnasium .-